Taxonomic study of the genus Araucanioperla Illies 1963 (Plecoptera: Gripopterygidae), with the description of the male genitalia, eggs and the last instar larva for A. brincki - Vera, Alejandro (Zootaxa, 2019)
A comparative study of morphology on the genus Araucanioperla Illies, 1963 is discussed. Two species of Araucanioperla are known, A. bullocki (Navás, 1933) and A. brincki (Froehlich, 1960). For the first time the larva of A. brincki, the male genitalia of A. bullocki and the eggs of the two species are described and illustrated. The results showed that the morphology of the larvae is similar for the genus, definitively rejecting other larval morphotypes proposed for it. Eggs are also similar between the two species. The male genitalia of both species are specifically distinctive.